Overview of The Vaccine Cold Chain System in Five Semarang City Health Centers - Dian Nintyasari Mustika; Sherkia Ichtiarsi Prakasiwi (Program Studi Kebidanan Fakultas Kedokteran Universitas Sebelas Maret, 2021)
Immunization is an effort to reduce morbidity rate, mortality rate, and birth defects in children. It is either a regular or supplemental program for PD3I or vaccine-preventable diseases such as TB, diphtheria, pertussis, tetanus, hepatitis B, polio, and rubella. An infant ideally receives a complete basic vaccine which consists of one dosage of BCG, three dosages of DPT, four dosages of Polio, three dosages of HB, and one dosage of MR. The immunization program is said to be effective and able to decrease the disease when the implementation is well completed and the immunization service quality is guaranteed based on the standard, especially the implementation of vaccine cold chain. The aim of this study is to investigate the condition of vaccine cold chain equipment at five community health centers in Semarang city.It was an observational descriptive research with a cross-sectional design conducted in five community health centers in Semarang city. The sampling technique used in this research was consecutive sampling. The respondents consisted of 5 vaccine managers at the community health center. The data were collected through a questionnaire which was then analyzed by using univariate analysis. It was found that most of the respondents (80.0%) did not provide a cold room in its building. Few respondents (40%) said that they provided the national standardized (SNI) and WHO’s Performance Quality and Safety (PQS) standardized vaccine refrigerator. Meanwhile, only 20% of the respondents stated that they provided the national standardized (SNI) and PQS standardized vaccine freezer. On the other hand, 60% of respondents explained that the tape on the thermostat vaccine refrigerator/freezer was already installed. The same result also happened in which 60% of respondents also explained that they provided Indonesian national standardized (SNI) and PQS standardized disposable or reusable cold packs. Further, 100% of respondents stated that they provided either vaccine carriers to carry out the vaccine to the immunization service site, cold packs and dry ice in the cold pack, or VVM as the temperature indicator such as thermometer and temperature record chart. It is expected that each health center has a refrigerator/ freezer vaccine according to SNI and PQS from WHO